2009
DOI: 10.1166/jns.2009.005
|View full text |Cite
|
Sign up to set email alerts
|

Metal Chelators Coupled with Nanoparticles as Potential Therapeutic Agents for Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a devastating neuro-degenerative disorder characterized by the progressive and irreversible loss of memory followed by complete dementia. Despite the disease's high prevalence and great economic and social burden, an explicative etiology or viable cure is not available. Great effort has been made to better understand the disease's pathogenesis, and to develop more effective therapeutic agents. However, success is greatly hampered by the presence of the bloodbrain barrier that limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 126 publications
(168 reference statements)
0
21
0
Order By: Relevance
“…However, the highest dose was well tolerated for 12 weeks and resulted in significantly lower cerebrospinal fluid Ab42 levels, and improved performance relative to baseline values on two executive function tests from the NTB (Faux et al 2010). While larger trials are required to further test the efficacy of PBT2, several novel compounds aimed at modulating zinc availability including targeted nanoparticles loaded with zinc or coupled to chelators are in the preclinical testing phase (Bush and Tanzi 2008;Liu et al 2009;Grabrucker et al 2011a).…”
Section: Therapies Aimed At Modulating Zinc Availabilitymentioning
confidence: 99%
“…However, the highest dose was well tolerated for 12 weeks and resulted in significantly lower cerebrospinal fluid Ab42 levels, and improved performance relative to baseline values on two executive function tests from the NTB (Faux et al 2010). While larger trials are required to further test the efficacy of PBT2, several novel compounds aimed at modulating zinc availability including targeted nanoparticles loaded with zinc or coupled to chelators are in the preclinical testing phase (Bush and Tanzi 2008;Liu et al 2009;Grabrucker et al 2011a).…”
Section: Therapies Aimed At Modulating Zinc Availabilitymentioning
confidence: 99%
“…This has been explored for delivery of nerve growth factor for Huntingon's disease (Kordower, et al, 1994). Nanocarriers have also been used as vehicles to assist in transporting chelating agents into the brain for iron capture and removal in Alzheimer's disease, also with potential in Huntington's and Parkinson's diseases (Liu, et al, 2009). Similar nanomedicine strategies can improve delivery of other small molecule therapies for genetic diseases, including hormones to control regulatory pathways, antibiotics, growth factors, cofactors, inhibitors or activators that act upstream or downstream of affected pathways, chaperones that favor proper protein folding, and other chemicals.…”
Section: Human Genetic Diseases 252mentioning
confidence: 99%
“…Transition metal chelator treatments in vivo and in vitro have shown promising results on the solubilization of A in logical function [18]. The current studies are focussing on nanoparticle delivery of chelation agents which can be possible treatment for AD [19]. Recently, a study was reported on lithium which shows decrease in both the production of A and tau phosphorylation and may improve memory on aluminium loaded rats [20].…”
Section: Metal Chelatorsmentioning
confidence: 99%